Genome-wide association analysis of agronomical and physiological traits linked to drought tolerance in a diverse potatoes (Solanum tuberosum) panel - Tagliotti, Martín Enrique (2021)
Potatoes is often considered a drought-sensitive crop and its sustainable production is threatened due to frequent drought episodes. Drought tolerance is a complex trait of increasing importance in potatoes therefore its yield is threatened. The differential response of several physiological and agronomical traits was evaluated in a diverse potatoes panel under contrasting water regimes to identify quantitative trait loci (QTL) associated with drought tolerance using genome-wide association analysis with 4859 high-quality SNP markers. Phenotypic data were collected from multiple environments and years. QTL with diverse linkage disequilibrium blocks for proline concentration, water consumption and yield were detected on chromosomes 1, 4 and 10. These QTL detected were associated with known gene functions. The current study provides insights into the putative genes that controlled the responses to the drought tolerance in potatoes at physiological and agronomical levels. The QTL described in this work might be included in future marker-assisted selection programmes linked with drought tolerance in potatoes.